Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.

- Republican31

Solve 3 – 2(b – 5) = 7. Or is the equation an Identity? Or if it has any solution at all? I want help to solve it more than the straight answer.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions.

Get your **free** account and access **expert** answers to this and **thousands** of other questions

- Republican31

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

so you just want to solve for b right?

- Republican31

Yes. If it is solvable.

- anonymous

okay so you can start of by distributing the -2 into (b - 5) do you know how to do that?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

- rhr12

b=12

- Republican31

Yes.
3-2b+10=7, right?

- anonymous

yes okay so now you can combine the 3 and the 10 into a 13

- anonymous

also b does not =12 @rhr12

- anonymous

okay so now you should have -2b + 13 = 7

- Republican31

Okay so 13-2b=7. Then subtract 13 from both sides?

- rhr12

(3-2)*{b(12)-5}=7
1*7=7
7=7

- rhr12

i used a different formula but i also like your formula @watchpencilpaper

- Republican31

-2b = -6. So then divide -6 by -2, making
b=3, correct?

- Republican31

@rhr12 that would make it an identity, correct? If it is correct, @watchpencilpaper?

- Republican31

If the equation is correct, I mean.

- anonymous

you cant subtract the 2 from the 3 before multiplying it by the (12-5) so its wrong

- anonymous

lets just continue solving the equation and then we can check our answer
so we left of at -2b = -6 right?

- Republican31

Yes. b=3?

- anonymous

yes okay and we can check that by plugging it back into our equation
\[3 - 2(b-5) = 7\]
\[3 - 2((3)-5) = 7\]
\[3 - 2(-2) = 7\]
\[3 - (-4) = 7\]
\[3 + 4 = 7\]
\[7 = 7\]

- Republican31

Alright! Thank you!

- anonymous

yep no problem :D

Looking for something else?

Not the answer you are looking for? Search for more explanations.